Decision Making in Surgical Oncology - Metin Yalaza (Turkish Journal of Colorectal Disease, 2018)
As can be seen from ancient Egyptian writings, cancer has been a major health problem for at least 3.500 years. Significant progress has been achieved in the battle against cancer in conjunction with increased knowledge and technological developments. However, cancer remains one of the leading causes of deaths worldwide. In the last century, as genetics and histopathological studies have fostered our understanding of the nature of the disease, oncology has become a subdiscipline within some of the major medical branches, i.e. surgical oncology. Several studies have been conducted on the decision-making process in cancer patients and it has been emphasized that correct decision-making is essential for proper management of the disease. In this article, we aimed to create a foundation based on what we already know on this important issue, to understand the difficulties of the decisionmaking process, and to emphasize the developments needed to overcome these difficulties.